A Framework for Multidisciplinary Optimization of a Balancing Mechanism for an Industrial Robot - Johan A. Persson; Xiaolong Feng; Daniel Wappling; Johan Ölvander (Journal of Robotics)
The paper presents a framework that can be used to design and optimize a balancing mechanism for an industrial robot. The framework has the capability to optimize three different concepts: a mechanical, a pneumatic, and a hydropneumatic. Several disciplines are included in the framework, such as dynamic and static analyses of the robot performance. Optimization is performed for each concept and the obtained optimal designs are all better than the reference design. This means that the framework can be used as a tool both to optimize the balancing mechanism and also to support concept selection.